Undernutrition and associated factors among older adults in Ethiopia: systematic review and meta-analysis - Amien Ewunetei; Getachew Arage; Hiwot Yisak; Melkalem Mamuye Azanaw; Melkamu Aderajew Zemene; Agmasie Tigabu Demelash; Denekew Tenaw Anley (BMJ Open, 2023)
Objective Undernutrition contributes to decreased physical and cognitive functional status, higher healthcare consumption, premature institutionalisation and increased mortality. So, the objective of this study was to determine the pooled prevalence and factors associated with undernutrition among older adults in Ethiopia.Design Systematic review and meta-analysis was used. Articles that presented original data on undernutrition using body mass index (BMI) were included. We made an inclusive literature search from PubMed, Medline and Google Scholar. The I2 test was used to examine the heterogeneity of the studies considered in this meta-analysis. Stata software V.14 and METANDI command were used.Setting Studies conducted in Ethiopia were included.Participants Eight independent studies were eligible and enrolled for final analysis.Outcome Prevalence and determinants of undernutrition. A selection of publications, data extraction and reported results for the review was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.Results A total of eight unique studies were enrolled for final analysis. The pooled prevalence of undernutrition was 20.53% (95% CI 17.39% to 23.67%). The study revealed that males had lesser odds of being undernutrition with AOR 0.17 (95% CI 0.15 to 0.20). Older adults in the age range of 65–74 years were less likely to be undernourished as compared with those whose age was above 85 years with Adjusted Odds Ratio (AOR) 022 (95% CI 0.22 to 0.25). Older adults who were depressed had higher odds of undernutrition as compared with their counterparts with AOR 1.27 (95% CI 1.19 to 1.37). However, older adults from households with poor wealth indexes were two times more likely to be undernourished as compared with those who were from rich households.Conclusion The burden of undernutrition in Ethiopia is significant. The limitation of the current study was that all included studies were observational, mainly cross-sectional.